Role of palmaris longus as a contributing factor in Carpal Tunnel Syndrome-Ultrasonographic evaluation of Median Nerve and Carpal canal diameter - Jagannath B Kamath; Babul Reddy; Nikil Jayasheelan; Amarnath D Savur (Wolters Kluwer Medknow Publications, 2014)
Purpose: To assess the diameter of Carpal tunnel (CT) and the Median Nerve (MN) in individuals with unilateral absence of Palmaris longus (PL) and compare it with the side with presence of Palmaris longus. Materials and Methods: Volunteers (students in the age group of 18-20 years) from a medical college were enrolled over a 2-month period, October to November 2007. Twenty-five subjects with unilateral absence of PL were selected for the study. We used the wrists with PL agenesis as cases and the contra lateral side with PL as controls. Anteroposterior (AP) and transverse diameters of carpal canal and MN were measured at both proximal (pisiform) level and distal (hook of the hamate) level with wrist in neutral position. Results: Significant differences were noted in the dimensions of Carpal canal and MN on the sides with PL as compared to the sides with PL agenesis. The difference in the CT AP diameter was very highly significant at proximal and distal level (P < 0.01) whereas the transverse diameter was significantly different at both the levels. The difference in MN AP diameter was highly significant at distal level. The MN transverse diameter was significantly different at both the levels. Conclusion: In our study we found that the PL tendon is independently associated with decreased CT and MN dimensions (AP > transverse). This study supports the previously done studies on the association between the Carpal Tunnel Syndrome (CTS) and presence of PL tendon.